Sentencing according to law / Zuraida Ismail - Ismail, Zuraida (Faculty of Law, 1987)
As a practical matter, the sentencing of those convicted is probably the most important part of the criming process. It is here that the criminal law has the "bite" on the individual. The most important issue on entering the criminal process is what will be their punishment. Sentencing also presents some of the most complex issues in the operation of the criminal system. The criminal serves a variety of purpose including deterrence, rehabilitation, prevention and perhaps retribution. It is the point of sentencing that these aims must be balanced against one another in reaching a concrete decision as to what should be done with a particular individual. If all of the aims of the criminal law pointed in the same direction, the decision would be easily made. In fact, however, things are not that simple. In the study, I have proposed to deal with certain aspects of sentencing in Malaysia. Sentencing is a very wide topic and it will be practically impossible to cover almost every aspect of it within the limited length of the study. Much material, information on sentencing in other countries, for example, America and England are available in this country.